The association of serum calprotectin with fitness indicators and biochemical markers in high-level athletes: A continuous dynamic monitoring during one competitive season - Bukvic, F.; Ivkovic, A.; Cicak, H.; Dukic, L.; Šimundic, A.-M.; Marijancevic, D.; Pašalic, D. (Sports, 2023)
The objective was to determine the associations between several biochemical indicators and the dynamics of concentration change across four physical fitness phases over the period of a competitive season. Furthermore, associations between serum calprotectin and biomarkers of inflammation or muscle injury and physical indicators were examined.